The impact of vaginal dilator use on vaginal stenosis and sexual quality of life in women treated with adjuvant radiotherapy for endometrial cancer = Einfluss der Anwendung eines Vaginaldilatators auf Vaginalstenose und sexuelle Lebensqualität nach adjuvanter Radiotherapie bei Frauen mit Endometriumkarzinom - Akbaba, Sati; Oelmann-Avendano, Jan Tobias; Krug, David; Arians, Nathalie; Bostel, Tilman; Hörner-Rieber, Juliane; Nicolay, Nils; Debus, Jürgen; Lindel, Katja; Förster, Robert (Strahlentherapie und Onkologie, 2019)
Despite a lack of evidence and low compliance, current guidelines recommend the use of a vaginal dilator (VD) after pelvic radiotherapy (RT). We analyzed the effect of VD on vaginal stenosis (VS) and its influence on sexual quality of life (QoL) in women treated with adjuvant RT for endometrial cancer (EC).
Gesehen am 09.03.2020